Role of serve and return of serve at European Games 2015 table tennis tournament - Djokic, Z.; Munivrana, G.; Levajac, D. (Proceedings Book of The 15th ITTF Sports Science Congress Düsseldorf, 27th - 28th May 2017, 2017)
The aim of this study was match analyses considering the efficacy of serve and return of serve in high level table tennis. Methods: The analysis of game was performed using official data from 46 matches played by 45 best European players in Men`s singles competition at European Games held in Baku 2015. Performance indicators were: playing on own serve (percentage of won and lost points on own serve) and return of serve (percentage of winning points on opponent serve). All games from 1st round till the final match were analysed (253 sets and 4649 played points). Players were analysed according match outcome (winners/ losers) and performance level (better/lower ranked). For all descriptive statistic parameters were calculated. The differences between winners and losers were analysed with independent samples t-test (p<.05), while differences according performance level and according phase of competition were tested using One-way ANOVA (p<.05). Results: Percentage of winners on their serve won point efficacy was 60.60±7.43% (in the range from 47.27 to 83.33%), lost points were 39.37±7.47% (16.17-52.73%) and won points on opponent serve was 53.28±6.73% (40.91-70.97%). Percentage of losers won point on their serve was 46.76±6.67% (29.03-59.09%), lost point`s 53.28±6.73% (40.91-70.97%) and won points on opponent serve 39.37±7.48% (16.17-52.73%). Statistically significant differences in efficacy (Winner/Loser) were identified in all analysed performance indicators. There were no significant differences according to the phase of competition and performance level. This study indicates that these activities can be monitored as a valuable performance indicators, especially in competition and confirm importance for the assessment of training.